Medeltida klostergrunder på Island - vegetation och flora, kultur och reliktväxter, samtida växtnamn - Larsson, Inger; Åsen, Per Arvid; Kristjánsdóttir, Steinunn; Lundquist, Kjell (2012)
Icelandic medieval monastic sites – vegetation and flora, cultural- and relict plants, contemporary plant-names The colonization of Iceland began in the late 9th century and in the year 1000 the Althing chose Christianity to replace paganism as the religion of the country. The bishopric of Skálholt was established in 1056 and Hólar in 1106. There are traces of twelve to fifteen monasteries, of which nine are recognized as having lasted for some time. Of these only Skriðuklaustur has been fully excavated, exhibiting a European building model. Viðeyjarklaustur and Kirkjubaejarklaustur have been partly excavated not revealing any specific monastic buildings as yet. Archaeobotanical investigations have only been undertaken on Viðey and at Skriðuklaustur. The exact localisation of the monastic buildings, or possible monastic cultivation. are only presumptions at all other places, as is the type of monastic building, whether traditional Icelandic farm type or continental monastery building type. The questions that this project seeks to answer are which cultivated plants on the whole, and garden plants in particular, were known and used in the medieval Icelandic monastic context, and whether it is possible to find medieval relict plants in connection with the Icelandic monastic sites. All monastic sites were surveyed for landscape and plants, and complete lists of the plants found are published in Bilaga 1. Medicinal, utility and ornamental plants, known in Iceland and abroad, have been recorded, but their status as true medieval monastic relict plants cannot be fully determined at this stage of research. The very special conditions in which a hitherto uninhabited island was colonized in some hundred years by people bringing and adapting their knowledge of farming, cultivating and using plants for both utility and pleasure led inevitably to a situation where common knowledge became integrated with the specific uses of plants and plant medicine in a monastic context. Many of the plants found today, such as Angelica, ...